PROPERTIES OF CONTACT SURFACES ON A WEAVING LOOM AND WAYS TO INCREASE THEIR PERFORMANCE (Web of Teachers: Inderscience Research, 2024)
The goal of the work is to increase the environmental safety of weaving equipment by reducing wear of contact surfaces. Minimizing wear and tear during the operation of weaving equipment is of great importance for the environment. However, the physicochemical interaction of metal surfaces with the environment in certain areas is uneven due to its polycrystalline structure and heterogeneity. In this case, the physical and chemical activity of individual surface grains is significantly influenced by the magnitude of their residual stresses (micro-stresses), the degree of plastic deformation, etc. The article studies the causes of wear on the baton mechanism of a shuttleless weaving loom as a result of friction, which leads to a noticeable increase in warp thread breaks and a decrease in the quality of raw fabric. To ensure the environmental safety of weaving equipment, methods have been proposed to increase the wear resistance of the drum mechanisms of shuttleless weaving machines. As a result of the research, it was found that the main reason for the destruction of surface layers is the occurrence of fatigue cracks and the separation of microscopic flakes of the material or its oxides. The work substantiates that an effective method for increasing the performance of the baton mechanisms of shuttleless type looms can be the method of surface plastic deformation of the inner surface of the shed of the baton teeth. As a result, the uniformity of the physical and chemical interaction of metal surfaces with the environment is ensured, as the resistance to wear and fatigue failure increases. This has a positive effect on the quality of the produced fabric and the productivity of the process due to the reduction in the breakage of warp threads during shockless high-speed sliding of the thread guide along the comb teeth.